Turkey’s Open-Door Policy for Syrian Regugees: Humanity Motive and Political Motive - Muhammad Dary Suryantama (UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. This article aims to analyse The Turkey Open-Door Policy for Syrian Refugees on two motives namely humanity and political. This policy has been done since the conflict in Syria escalated and that ‘forces’ Turkey to do the Open-Doors Policy. Many stated that the motive of this policy is driven by religion motive, which is Islam, and geographical factor between both countries. But in practice it seems not enough to explain a whole Turkey’s action on implementing the Open-Door Policy. Probably there are other motives that have driven Turkey to receive the Syrian Refugees but we can say that if Turkey has implemented the Open-Door Policy, it means Turkey is ready to take care of Syrian Refugees with its economic resource and land space. This article analyses three problem formulations: what is turkey’s humanity and political motive in Open-Door policy, how Turkey treat Syrian Refugees considering that Turkey is also at war with the Syrian Kurds? what the advantage and disadvantage faced by Turkey in doing the Open-Door policy? This article used qualitative & descriptive methods and it used secondary data obtained from several journals and books. The conclusion stated Turkey has a limit to received Syrian Refugees even the President of Turkey, Recep Tayyip Erdoğan had admitted it. And there is a political motive besides humanity motive behind the policy. The condition of refugees not very well in the refugee shelter. If every side wants to end the flow of refugee, therefore every sides should help Syria end Its terrible conflict. Keywords: Syrian Refugees, Turkey, Open-Door Policy, humanity motive, political motive. Abstrak. Artikel ini bertujuan untuk menganalisis kebijakan Pintu-Terbuka Turki untuk pengungsi Suriah pada dua motif yaitu kemanusiaan dan politis. Kebijakan ini telah dilakukan sejak konflik di Suriah meningkat dan itu ‘memaksa’ Turki untuk melakukan kebijakan Pintu-Terbuka. Banyak yang menyatakan bahwa motif kebijakan ini didorong oleh motif agama, yakni Islam, and faktor geografi antara kedua negara. Namun secara praktis sepertinya itu tidak cukup untuk menjelaskan seluruh perilaku Turki pada implementasi kebijakan Pintu-Terbuka. Mungkin ada motif lain yang mendorong Turki untuk menerima pengungsi Suriah tetapi dapat kita katakan jika Turki Telah mengimplementasikan kebijakan Pintu-Terbuka, itu artinya Turki siap untuk menjaga pengungsi Suriah dengan sumber daya ekonomi dan wilayahnya. Artikel ini menganalisis tiga rumusan masalah: apa motif kemanusiaan dan politis pada kebijakan Pintu-Terbuka? bagaimana Turki memperlakukan pengungsi Suriah mempertimbangkan bahwa Turki juga dalam perang dengan Kurdi Suriah? apa keuntungan dan kerugian yang dihadapi Turki dalam melakukan kebijakan Pintu-Terbuka?. Artikel ini menggunakan metode kualitatif & deskriptif dan menggunakan data sekunder yang diperoleh dari berbagai jurnal dan buku. Kesimpulan menyatakan bahwa Turki memiliki batasan untuk menerima pengungsi Suriah bahkan Presiden Turki, Recep Tayyip Erdoğan telah mengakuinya. Dan terdapat sebuah motif politik dibalik motif kemanusiaan di belakang kebijakan. Kondisi para pengungsi tidak terlalu baik dalam penampungan. Jika seluruh pihak hendak mengakhiri arus dari pengungsi, maka seluruh pihak seyogianya membantu Suriah mengakhiri konflik-Nya yang parah.Kata Kunci: Pengungsi Suriah, Turki, Kebijakan Pintu-Terbuka, motif kemanusiaan, motif politik.